Effect of turmeric (Curcuma longa L.) on blood glucose control in patients with diabetes mellitus - Ranti Ningsih Sumarni; Atik Aryani; Fajar Alam Putra; Laras Adi Rantika Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diabetes mellitus (DM) cases remain a global concern. DM is often referred to as the